MAPPING OF SALTWATER INTRUSION AT IGBOKODA, SOUTHWESTERN, NIGERIA USING COMBINED GEOPHYSICAL AND CHEMICAL TECHNIQUES - JAMES ADEGOKE (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2018)
This research work was set out to map saltwater intrusion in Igbokoda area of Ilaje, Ondo State, Southwestern, Nigeria using combined geophysical and chemical techniques. Eight (8) Vertical Electrical sounding were carried out using the Schlumberger Electrode array system with maximum spread of (AB/2) 133 m and water samples were acquired and analysed using atomic absorption spectrometer. The VES data was interpreted by the method of partial curve matching and computer iteration technique using Winresist software. The result obtained revealed four geoelectric layers. The saltwater intrusion originated from movement of seawater into the freshwater aquifer coupled with human activities.